Application of Rhizoctonia mycorrhiza and without Rhizoctonia mycorrhiza in improving vegetative growth of Dendrobium nindii seedlings - Soelistijono, R; Daryanti, Daryanti; Mardhikasari, Siti; Sari, Tyara Yunika; Rakhmawati, Dian (Jurusan Agroteknologi, 2023)
Dendrobium is a genus of orchid that has the most attraction among the public rather than other types, especially for orchid species such as Dendrobium nindii type. The obstacle in cultivating orchids species is the slow vegetative growth when compared to orchids resulting from crosses (hybrid orchids). This research aimed to determine the vegetative growth of D. nindii seedlings using Rhizoctonia sp. The research was conducted at the Greenhouse, Faculty of Agriculture, Tunas Pembangunan University from January to July 2023. The research used quantitative descriptive method consisting of one treatment with six replications and each replications contained ten plants. The factor was application of Rhizoctonia mycorrhiza and without application of Rhizoctonia mycorrhiza. The results showed that (1) the morphological characteristics of Rhizoctonia mycorrhiza were white colonies, with right-angled branches and two nuclei, (2) the application of mycorrhizal Rhizoctonia had a very significant effect on the vegetative growth of D. nindii as shown in the parameters of plant height, leaf length, number of leaves, root length, number of roots and fresh weight of seedlings, and (3) there was an association of Rhizoctonia mycorrhiza with the formation of the peloton structure.ABSTRAKDendrobium merupakan salah satu genus anggrek yang memiliki daya tarik paling banyak di masyarakat diantara jenis anggrek lainnya terutama untuk anggrek spesies seperti Dendrobium nindii. Kendala dalam budidaya anggrek spesies adalah pertumbuhan vegetatif yang lambat bila dibandingkan dengan anggrek hasil persilangan (anggrek hibrida). Penelitian ini bertujuan untuk mengetahui pertumbuhan vegetatif bibit D. nindii dengan menggunakan Rhizoctonia sp. Penelitian dilakukan di Rumahkasa Fakultas Pertanian Unversitas Tunas Pembangunan dari Januari sampai Juli 2023. Penelitian menggunakan metode deskriptif kuantitatif dengan enam ulangan dan setiap ulangan terdiri enam tanaman. Faktor perlakuan adalah aplikasi Rhizoctonia mikoriza dan tanpa aplikasi Rhizoctonia mikoriza. Hasil penelitian menunjukkan (1) ciri morfologi Rhizoctonia mikoriza berupa koloni berwarna putih, dengan percabangan siku-siku dan berinti dua, (2) pemberian Rhizoctonia mikoriza berpengaruh sangat nyata pada pertumbuhan vegetatif D. nindii Â yang ditunjukan pada parameter tinggi tanaman, panjang daun, jumlah daun, panjang akar, jumlah akar dan berat segar bibit, dan (3) terjadi asosiasi Rhizoctonia mikoriza dengan terbentuknya struktur peloton.